A Literacy and Numeracy Model to Enhance the Independent Learning Education for Islamic Elementary School Teachers - Ahwy Oktradiksa; Mujahidun Mujahidun; Carolyn Hunt (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis study aims to determine the effectiveness of the literacy-numeration model in increasing educational learning independence for class teachers and students at Madrasah Ibtidaiyah, Magelang Regency, Indonesia. Qualitative and quantitative approaches were used as research methods. Data were collected by using interviews, observation, and documentation techniques. The collected data were then analysed with hypothesis test, validity, reliability, normality, paired t-test, and simple independent-test. This research was conducted on a subject population of 43 Madrasah Ibtidaiyah class teachers. The results showed the effectiveness of the development of independent learning education with literacy and numeracy models for class teachers and students of Madrasah Ibtidaiyah in Magelang Regency, Indonesia. The results of the output test